Determinants Of Reputable Underwriters In Green Bond Offering - Najar, Nazlen Lydia MD; Ling, Tai-Hu; Ooi, Ai-Yee (STIE Malangkucecwara, 2024)
This research paper delves into the process by which industrial companies issuing green bonds can secure certification from reputable underwriters. By analyzing data from international green corporate bond offerings from the period between 2014 and 2022, the study aims to unravel the factors that influence underwriter selection decisions. Using a logit model to address the potential biases, the research reveals specific firm and bond characteristics that significantly impact the likelihood of collaborating with reputable underwriters. The findings indicate that reputable underwriters exhibit a preference for larger firms demonstrating strong financial performance, dealing with larger bond sizes, and possessing distinct bond features such as callability and involvement in private placements. Additionally, variables like maturity periods, involvement in finance vehicles, credit ratings, and syndicate size emerge as crucial factors in underwriter selection processes. These insights highlight the critical factors that issuers must thoroughly assess when selecting underwriters with strong reputations. The significance role of underwriter credibility, capabilities, and reliability in shaping the landscape of green bond underwriting is emphasized. This analysis holds relevance for both academic research and industry practitioners within the realm of sustainable finance.